Cytotoxic response of tumor-infiltrating lymphocytes of head and neck cancer slice cultures under mitochondrial dysfunction - Greier, Maria do Carmo; Runge, Annette; Dudas, Jozsef; Hartl, Roland; Santer, Matthias; Dejaco, Daniel; Steinbichler, Teresa Bernadette; Federspiel, Julia; Seifarth, Christof; Konschake, Marko; Sprung, Susanne; Sopper, Sieghart; et al. (Frontiers in Oncology, 2024)
Background Head and neck squamous cell carcinomas (HNSCC) are highly heterogeneous tumors. In the harsh tumor microenvironment (TME), metabolic reprogramming and mitochondrial dysfunction may lead to immunosuppressive phenotypes. Aerobic glycolysis is needed for the activation of cytotoxic T-cells and the absence of glucose may hamper the full effector functions of cytotoxic T-cells. To test the effect of mitochondrial dysfunction on cytotoxic T cell function, slice cultures (SC) of HNSCC cancer were cultivated under different metabolic conditions. Methods Tumor samples from 21 patients with HNSCC were collected, from which, SC were established and cultivated under six different conditions. These conditions included high glucose, T cell stimulation, and temporarily induced mitochondrial dysfunction (MitoDys) using FCCP and oligomycin A with or without additional T cell stimulation, high glucose and finally, a control medium. Over three days of cultivation, sequential T cell stimulation and MitoDys treatments were performed. Supernatant was collected, and SC were fixed and embedded. Granzyme B was measured in the supernatant and in the SC via immunohistochemistry (IHC). Staining of PD1, CD8/Ki67, and cleavedcaspase3 (CC3) were performed in SC. Results Hematoxylin eosin stains showed that overall SC quality remained stable over 3 days of cultivation. T cell stimulation, both alone and combined with MitoDys, led to significantly increased granzyme levels in SC and in supernatant. Apoptosis following T cell stimulation was observed in tumor and stroma. Mitochondrial dysfunction alone increased apoptosis in tumor cell aggregates. High glucose concentration alone had no impact on T cell activity and apoptosis. Apoptosis rates were significantly lower under conditions with high glucose and MitoDys (p=0.03). Conclusion Stimulation of tumor-infiltrating lymphocytes in SC was feasible, which led to increased apoptosis in tumor cells. Induced mitochondrial dysfunction did not play a significant role in the activation and function of TILs in SC of HNSCC. Moreover, high glucose concentration did not promote cytotoxic T cell activity in HNSCC SC.